Immune Checkpoint Markers in Neuroendocrine Carcinoma of the Digestive System - Xing, Jiazhang; Ying, Hongyan; Li, Ji; Gao, Yang; Sun, Zhao; Li, Jiarui; Bai, Chunmei; Cheng, Yuejuan; Wu, Huanwen (Frontiers in Oncology, 2020)
Digestive system neuroendocrine carcinomas (NECs) are rare neoplasms originating from neuroendocrine cells with a poor prognosis and limited effective treatments. Programmed cell death protein 1/ligand 1 (PD-1/PD-L1) blockade has been used in the management of more than 10 solid tumors and has achieved promising clinical outcomes. PD-L1 expression, immune cell infiltration, tumor mutational burden (TMB) and microsatellite instability (MSI) are all verified biomarkers that can predict the response to anti-PD-1/PD-L1 therapy. Here, we investigated PD-L1 expression and immune cell infiltration density by immunohistochemical (IHC) staining of tumor samples from 33 patients with digestive system NECs. Tumor and paratumor normal samples from 31 of these patients underwent whole-exome sequencing to evaluate TMB and the MSI-high (MSI-H) status. In total, 29.0% of digestive system NECs had positive PD-L1 expression according to the tumor proportion score (TPS). Infiltration of CD3+, CD8+ and CD68+ cells was observed in 69.7%, 27.3% and 54.5% of patients, respectively. The TMB value for patients sequenced ranged from 0.57 to 11.75 mutations/Mb, with a median of 5.68 mutations/Mb. mSINGS, MSIsensor and MSIseq were used to analyze the MSI status according to the sequencing data, and in our evaluation, no MSI-H status was detected. Our data might indicate a limited potential of anti-PD-1/PD-L1 monotherapy in digestive system NECs, although clinical trials are warranted.